1987
DOI: 10.1111/j.1365-2125.1987.tb03081.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine‐induced respiratory stimulation in man depends on site of infusion. Evidence for an action on the carotid body?

Abstract: Adenosine is an endogenous nucleoside which stimulates respiration in man and other mammals. In animals adenosine appears to initiate respiratory stimulation within the carotid body, but whether this is the site of action in man is not known. We administered adenosine by intra-aortic infusion to 12 subjects undergoing cardiac catheterisation. When adenosine was infused at three sites proximal to the carotid circulation, minute ventilation was significantly higher than baseline values or those during adenosine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(57 citation statements)
references
References 18 publications
1
55
1
Order By: Relevance
“…Since the response in MSNA did not differ significantly be tween LBNP and adenosine, involvement of the baroreflex could still account for the residual increase in MSNA but not for the residual heart rate response, since this was markedly different from the response to LBNP. Adenosine increases tidal volume Watt et al 1987;Smits et al 1987b) and thereby stimulates pulmonary stretch receptors. However, the heart rate response to adenosine is not affected by pulmonary denervation in humans, indicating that these receptors are not involved in the heart rate response to adeno sine (Morgan-Hughes et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Since the response in MSNA did not differ significantly be tween LBNP and adenosine, involvement of the baroreflex could still account for the residual increase in MSNA but not for the residual heart rate response, since this was markedly different from the response to LBNP. Adenosine increases tidal volume Watt et al 1987;Smits et al 1987b) and thereby stimulates pulmonary stretch receptors. However, the heart rate response to adenosine is not affected by pulmonary denervation in humans, indicating that these receptors are not involved in the heart rate response to adeno sine (Morgan-Hughes et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…1 Intravenous adenosine produces vasodilatation in coronary and noncoronary vascular beds, which typically decreases mean blood pressure (BP) a -10% to -15% during stable hyperemia. 2 Nevertheless, observational 3,4 and experimental studies [5][6][7] have observed a large interpatient variability in the BP response to intravenous adenosine, with most patients developing mild hypotension, whereas in others, BP profoundly decreases during stable hyperemia. The possible relevance of these varying BP responses to intravenous adenosine for stenosis assessment with FFR, however, has been barely addressed in the literature.…”
mentioning
confidence: 99%
“…The value calculated on placebo for the mean slope of the regression of ventilation upon PET,CO 2 Hyperoxic, hypercapnic responses were studied in an attempt to elucidate central adenosine-related mechanisms. The carotid bodies in animals [12,13], and also probably in humans [4,5], are stimulated directly by adenosine. Centrally-mediated respiratory depression by adenosine has also been observed in animals [14].…”
Section: Discussionmentioning
confidence: 99%
“…These drugs would be expected to enhance and attenuate adenosine-related mechanisms, respectively. The presence of hyperoxia is important in these experiments as, under these conditions, afferent activity from the carotid bodies (a site at which exogenous [4,5] and endogenous [3] adenosine may stimulate breathing) is attenuated.…”
mentioning
confidence: 99%